Use of MRI in the diagnosis of fetal brain abnormalities in utero (MERIDIAN): a multicentre, prospective cohort study - Griffiths, Paul D; Bradburn, Michael; Campbell, Michael J; Cooper, Cindy L; Graham, Ruth; Jarvis, Deborah; Kilby, Mark D; Mason, Gerald; Mooney, Cara; Robson, Stephen C; Wailoo, Allan (The Lancet (British edition), 2017)
In-utero MRI (iuMRI) has shown promise as an adjunct to ultrasound but the comparative diagnostic performance has been poorly defined. We aimed to assess whether the diagnostic accuracy and confidence of the prenatal diagnosis of fetal brain abnormalities is improved with iuMRI and assess the clinical impact and patient acceptability of iuMRI. We did a multicentre, prospective, cohort study in the UK, at 16 fetal medicine centres, of pregnant women aged 16 years or older whose fetus had a brain abnormality detected by ultrasound at a gestational age of 18 weeks or more, had no contraindications to iuMRI, and consented to enter the study. Women carrying a fetus suspected of having a brain anomaly on ultrasound had iuMRI done within 14 days of ultrasound. The findings were reviewed by two independent panels and used to estimate diagnostic accuracy and confidence by comparison with outcome diagnoses. Changes in diagnosis, prognosis, and clinical management brought about by iuMRI and patient acceptability were assessed. Participants were recruited between July 29, 2011, and Aug 31, 2014. The cohort was subdivided by gestation into the 18 weeks to less than 24 weeks fetus cohort (n=369) and into the 24 weeks or older fetus cohort (n=201). Diagnostic accuracy was improved by 23% (95% CI 18–27) in the 18 weeks to less than 24 weeks group and 29% (23–36) in the 24 weeks and older group (p<0·0001 for both groups). The overall diagnostic accuracy was 68% for ultrasound and 93% for iuMRI (difference 25%, 95% CI 21–29). Dominant diagnoses were reported with high confidence on ultrasound in 465 (82%) of 570 cases compared with 544 (95%) of 570 cases on iuMRI. IuMRI provided additional diagnostic information in 387 (49%) of 783 cases, changed prognostic information in at least 157 (20%), and led to changes in clinical management in more than one in three cases. IuMRI also had high patient acceptability with at least 95% of women saying they would have an iuMRI study if a future pregnancy were complicated by a fetal brain abnormality. iuMRI improves diagnostic accuracy and confidence for fetal brain anomalies and leads to management changes in a high proportion of cases. This finding, along with the high patient acceptability, leads us to propose that any fetus with a suspected brain abnormality on ultrasound should have iuMRI to better inform counselling and management decisions. National Institute for Health Research Health Technology Assessment programme.